PENINGKATAN SKILLS PASSING BAWAH BOLA VOLI MELALUI METODE RECIPROCAL TEACHING PADA PESERTA DIDIK KELAS X TAV-1 SMK NEGERI 2 GARUT TAHUN PELAJARAN 2021/2022 - ICA SANTANA (VOCATIONAL: Jurnal Inovasi Pendidikan Kejuruan, 2022)
Physical education is a vehicle for education, which provides opportunities for children to learn important things. Therefore, Physical Education Lessons are no less important than other lessons. The purpose of this research is to find out whether the Reciprocal Teaching method can improve the skills of volleyball underpassing techniques in class X students. Audio Video Techniques 2 SMKN 2 Garut in the 2019/2020 academic year? Data collection techniques are obtained through observations made by teachers and students where in making observations there are predetermined signs, to avoid things that are subjectivity from observation or observe. The stages of this research consist of four stages, namely Plan, Action, Observation and Reflection. The subjects in this study were students of class X. TAV-1 SMK Negeri 2 Garut, totaling 36 students. Based on the results of the study, it is known that the results of the initial data to the third cycle have an increase of 292 times and an average of 8.11. Active students in cycle III amounted to 27 students or about 75%, when viewed from the initial data there was an increase of 22 students or 61.11%. The results of this study can be concluded that "The Reciprocal Teaching Method can improve the skills of passing down volleyball techniques in class X. TAV-1 SMKN 2 Garut in the 2021/2022 academic year. The application of the Reciprocal Teaching method has a positive impact on the development and progress of students in following the teaching and learning process. ABSTRAKPendidikan Jasmani merupakan wahana pendidikan, yang memberikan kesempatan bagi anak untuk mempelajari hal-hal yang penting. Oleh karena itu, Pelajaran Penjas tidak kalah penting dibandingkan dengan pelajaran lain.Tujuan penelitian ini untuk mengetahui apakah metode Reciprocal Teaching dapat meningkatkan Skills teknik passing bawah bola voli pada siswa kelas X. Tehnik Audio Video-2 SMKN 2 Garut Tahun Pelajaran 2019/2020?.Tehnik pengumpulan data diperoleh melalui observasi yang dilakukan guru, dan siswa dimana dalam melakukan observasi ada rambu-rambu yang telah ditentukan sebelumnya, untuk menghindari hal-hal yang bersifat subyektivitas dari pengamatan atau observe. Tahapan penelitian ini terdiri atas empat tahap, yaitu Rencana, Tindakan, Pengamatan dan Refleksi. Subyek dalam peniltian ini adalah Peserta Didik kelas X. TAV-1 SMK Negeri 2 Garut yang berjumlah 36 Peserta Didik. Berdasarkan hasil penelitian diketahui bahwa hasil data awal ke siklus III ada kenaikan 292 kali dan rata-rata 8,11. Siswa aktif pada siklus III berjumlah 27 siswa atau sekitar 75%, bila dilihat dari data awal ada kenaikan 22 siswa atau 61,11%. Hasil penelitian ini dapat disimpulkan bahwa “Metode Reciprocal Teaching dapat meningkatkan Skills teknik passing bawah bola voli pada siswa kelas X. TAV-1 SMKN 2 Garut Tahun Pelajaran 2021/2022. Dalam Penerapan metode Reciprocal Teaching mempunyai dampak yang positif bagi perkembangan dan kemajuan siswa dalam mengikuti proses belajar mengajar.